Agency Building with Early Research Exposure: A Study of an Undergraduate Science Education Exposure Program - Deepika Bansal; Deepa Chari (Journal of Research in Mathematics, Science, and Technology Education, 2024)
Undergraduate research exposure provides students with opportunities to positively perceive their association with their scientific discipline through agentic experiences, and thereby fostering their disciplinary identity building. In the present study, we explore students’ experiences of participating in an undergraduate level research exposure camp in Chemistry discipline. The camp is organized under a national level nurture initiative for undergraduate science and engineering students in India. It is a two-week long residential camp in which students are engaged in lectures on theoretical topics in chemistry, problem solving sessions, long laboratory exercises, abstract writing session, and students’ seminars. The camp also serves as a first step to select a small cohort of students based on their performance in the different activities during the camp for extended research projects opportunities. We apply the critical science agency framework to examine students’ experiences during the camp, and how understand how students connect their prior experiences and future career related choices with their camp experiences. The qualitative analysis describes students’ accounts of the emergence of agentic personalities at the entry, during, and beyond the camp. We noted instances in which students’ decisions and subsequent actions of applying to and attending the camp surfaced, and through students’ narration interpreted how some of these were markers of critical science agency. Based on authors’ understanding, this is the first, and one of the few studies conducted using critical science agency framework with science undergraduate students about their early research experiences. The study provides insights about potential programmatic features for similar undergraduate research camps in India as well as on a global platform.